Qallunaat Crossing: The Southern-Northern Divide and Promising Practices for Canada's Inuit Young People - Moore, Shannon; Tulk, Wende; Mitchell, Richard (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2005)
Life for Inuit communities in Canada’s northern territory of Nunavut has been impacted by rapid change over the past fifty years in particular, a pattern that has similarly impacted First Peoples’ communities across the southern portion of the country for centuries. Unfortunately, inadequate resources often leave young people from Nunavut challenged to safely navigate these abrupt changes within their communities and culture. The chronic lack of resources for young people is compounded by the lack of educational opportunities for Inuit adults to enter professional roles in support of the region’s next generation. As a result, non-Inuit (or Qallunaat) professionals from southern Canada are frequently recruited. This paper examines some of the challenges faced by Inuit communities and Qallunaat professionals as they traverse the North/South divide within a cross-cultural educational context. This process is characterized by struggles and joy in finding the balance between meeting young people’s basic social and emotional needs, and professionals who are often illprepared to teach and learn within a cultural context with which they have little familiarity. In response, the authors describe some of the unique attributes of Inuit life and some of the many challenges faced by young people. They also suggest that a “ transdisciplinary” approach be established (Holmes and Gastaldo, 2004) towards educating Qallunaat professionals as an important step in achieving effective practice within northern communities- one which integrates knowledge from Inuit Elders with cross-cultural counseling techniques, multicultural competency development and practice-based wisdom. Specific application of these skills will be explored in this paper to illustrate ways of engaging “multiculturalism” within this context while accounting for the right of Canada’s Inuit young people to have their basic social, emotional and cultural needs recognized during a transformative historical epoch.